Influence of Front Contact Layer on the Performance of Bismuth-Based Perovskite Solar Cells - Faruk Sani; Sanusi Abdullahi (Physics Access, 2022)
Numerical analysis has been carried out using SCAPS-1D to investigate the power conversion efficiency of bismuth-based perovskite solar cells employing various Transparent Conductive Oxides (TCOs) such as Molybdenum Trioxide (MoO3), Boron-doped Zinc Oxide (BZO) and Zinc Oxide (ZnO). For the initial simulation, the power conversion efficiencies obtained for MoO3, BZO and ZnO were 0.24 %, 0.17 % and 0.17 % respectively. The influence of thickness, donor concentration and working temperature of the TCOs were varied to study their impact on the device’s photovoltaic performance. By varying the thickness, doping concentration and operating temperature, the electrical parameters observed for the three selected TCOs exhibited insignificant impact on the device’s performance. However, the highest performance was achieved using MoO3 at the thickness of 200 nm, donor concentration of 1 × 10 cm^3 and the operating temperature of 300 K with the corresponding power conversion efficiency of 0.24%, Jsc, Voc and FF of 0.2610 mA/cm2, 1.6509 V and 54.97% respectively. The numerical simulation shows the potential of designing and fabricating an improved bismuth-based perovskite solar cell with MoO3 as front contact as an alternative to Fluorine-doped Tin Oxide (FTO) and Indium-doped Tin Oxide (ITO).